TELAAH GENDER DALAM ISLAM PERSPEKTIF AMINA WADUD - Saepulrohman, Aziz; sopwandin, iwan (Mazalat: Jurnal Pemikiran Islam, 2023)
The issue of gender is one of the actual issues in Islam. In patriarchal culture, men are dominant in household matters. They make a living and make decisions in the family. Women's duties are only to obey and take care of domestic work at home. Instead, public space belongs to men. Women are seen as weak creatures who will always be below men. This view was born not only because of patriarchal culture, but also because of an understanding of the verses of the which is gender biased, causing injustice to women. Amina Wadud, one of the modern thinkers, challenged this understanding and advocated a reinterpretation of verses that were considered discriminatory against women. According to Wadud, in Islam, men and women have equal status. There is no superiority of men over women because the measure of glory is based on the quality of piety to Allah SWT, not on the basis of gender. Furthermore, Wadud also rejected the view of the majority of scholars who understand the word "nafsin wahidah" contained in Q.S. al-Nisa: 1 as Adam. The implication is that the creation of Eve which refers to the word "zawj" in the same verse did not come from Adam. According to him, Eve was created from matter of the same quality as the creation of Adam.